2011
DOI: 10.1095/biolreprod.110.085167
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GR-1 Stimulates Colony-Stimulating Factor 3 (Granulocyte) (CSF3) Output in Placental Trophoblast Cells in a Fetal Sex-Dependent Manner1

Abstract: Bacterial vaginosis is associated with a 1.4-fold increased risk of preterm birth. We have shown previously that Lactobacillus rhamnosus GR-1 supernatant up-regulates interleukin 10 and down-regulates tumor necrosis factor-alpha output in lipopolysaccharide (LPS)-treated human primary placenta cultures in a fetal sex-dependent manner. We hypothesize that lactobacilli also exert their anti-inflammatory effect by up-regulation of colony-stimulating factor 3 (granulocyte) (CSF3), which is secreted from both immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…Other studies have also shown evidence of sexual dimorphism in the biology of the placenta. Yeganegi et al have demonstrated that the key cytokine response of placental trophoblasts to lipopolysaccharide or endotoxin was greater in male fetuses [51], and that up-regulation of colony-stimulating factor 3 (CSF3) in trophoblasts by Lactobacillus rhamnosus GR-1 was detected only in trophoblasts obtained from placentas of female fetuses [52]. Murphy et al have shown that placental 11β-hydroxysteroid dehydrogenase activity differs between male and female fetuses in humans [53].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown evidence of sexual dimorphism in the biology of the placenta. Yeganegi et al have demonstrated that the key cytokine response of placental trophoblasts to lipopolysaccharide or endotoxin was greater in male fetuses [51], and that up-regulation of colony-stimulating factor 3 (CSF3) in trophoblasts by Lactobacillus rhamnosus GR-1 was detected only in trophoblasts obtained from placentas of female fetuses [52]. Murphy et al have shown that placental 11β-hydroxysteroid dehydrogenase activity differs between male and female fetuses in humans [53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is a strong association between elective preterm delivery (usually undertaken because of growth restriction or preeclampsia) and ischemic heart disease. 57 It should be noted that probiotics have not been proven clinically to reduce the risk of these complications in pregnancy, but as presented in Table I, 46,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] there are a number of attributes of these organisms that could play a role.…”
Section: Environmental Influences On Pregnancymentioning
confidence: 99%
“…Changes in diet provide distinctive signature of sexually dimorphic genes in placenta with expression generally higher in female than male placentas (9). The male placenta has higher TLR4 expression and a greater production of TNFα in response to LPS than the female placenta, which may underlie the propensity to preterm birth in males (10). …”
Section: Introductionmentioning
confidence: 99%